Heteroatom-doped honeycomb carbon covalent coupling cobalt / cobalt telluride heterojunction nano composite material as well as preparation method and application of heteroatom-doped honeycomb carbon covalent coupling cobalt / cobalt telluride heterojunction nano composite material
By using heteroatom-doped honeycomb carbon covalently coupled cobalt/cobalt telluride heterojunction nanocomposites as positive electrode electrocatalysts in lithium sulfur batteries, the problem of slow insulating properties and reaction kinetics of sulfur in lithium sulfur batteries is solved. , achieving efficient catalytic activity and excellent electrochemical properties.
Patent Information
- Application Number
- CN202411352865.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-09-26
AI Technical Summary
The existing lithium-sulfur batteries have severe shuttle effects due to the slow insulation and reaction kinetics of sulfur, which limits their commercial application potential.
Heteroatom-doped honeycomb carbon covalently coupled cobalt/cobalt telluride heterojunction nanocomposite is used as the positive electrode electrocatalyst for lithium sulfur batteries. Catalytic activity is improved by adjusting the distribution and size of the metal organic frame on the honeycomb carbon.
It significantly improves the electrochemical performance and cycle stability of lithium-sulfur batteries, enhances catalytic activity, and is suitable for high energy density lithium-sulfur batteries.
Smart Images

Figure CN119400863A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nanocomposite materials, and in particular to a heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material, a preparation method and application thereof. Background Art
[0002] As the country pays more and more attention to environmental protection issues, the development of clean energy is inseparable from environmentally friendly energy storage devices. As we all know, the advent of lithium-ion batteries has brought a lot of convenience to our daily lives, such as the use of mobile phones, laptops and other micro-electronic products.
[0003] However, with the development of science and technology and the improvement of quality of life, lithium-ion batteries cannot meet people's current needs due to their limited energy density, so it is becoming more and more urgent to develop energy storage devices with higher energy density.
[0004] Lithium-sulfur batteries are considered to be the next generation energy storage system with the most application prospects due to their high theoretical energy density (2600Wh Kg-1), abundant sulfur reserves, low price and environmental friendliness. However, lithium-sulfur batteries have the potential for commercial application seriously restricted by the insulating property of sulfur, slow reaction kinetics and severe shuttle effect. Therefore, the development of catalytic materials that can promote the conversion of lithium polysulfide is of great research significance to improve the electrochemical performance of lithium-sulfur batteries.
[0005] Porous carbon loaded with highly exposed active sites is a lithium-sulfur battery catalyst with great application potential, because porous carbon not only has abundant multi-level pores and a larger specific surface area, which can achieve high sulfur loading storage and provide sufficient attachment space for sulfur conversion reactions, but also can significantly improve the conductivity of the electrode and achieve rapid electron transfer.
[0006] However, the currently reported methods for preparing porous carbon are complex and expensive. Therefore, it is very important to develop conductive carbon materials that are simple to synthesize and inexpensive. Among them, metal heterojunction catalysts are considered to be one of the efficient active sites in lithium-sulfur batteries. However, as more and more metal elements are studied and the research scope becomes wider and wider, it is necessary to explore some effective methods to further improve the catalytic activity of heterojunction catalysts. Summary of the invention
[0007] The present invention is made to solve the above-mentioned problems, and aims to provide a heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material, a preparation method and its application, which has important promoting significance for the design of high catalytic activity heterojunction materials and the development of lithium-sulfur batteries.
[0008] The present invention provides a method for preparing a heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material, which has the following characteristics and comprises the following steps:
[0009] Step S1, dissolving and mixing citrate and nitrogen-containing small molecules, and subjecting them to evaporation, carbonization, and etching to obtain heteroatom-doped honeycomb carbon;
[0010] Step S2, dissolving the heteroatom-doped honeycomb carbon in a mixed solvent and stirring it evenly, then adding an organic ligand to the evenly stirred solution to react, and obtaining a metal organic framework / heteroatom-doped honeycomb carbon nanocomposite material after the reaction;
[0011] Step S3, placing the metal organic framework / heteroatom doped honeycomb carbon nanocomposite material in a porcelain boat, transferring it to the downstream of the tube furnace, placing tellurium powder upstream of the tube furnace, and calcining it in an inert gas atmosphere to obtain a heteroatom doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material,
[0012] Wherein, in step S3, the mass ratio of the metal organic framework / heteroatom doped honeycomb carbon nanocomposite material to the tellurium powder is 1.5 to 2.5.
[0013] In the preparation method of the heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material provided by the present invention, the following characteristics may also be provided: wherein, in step S1, the molar ratio of citrate to nitrogen-containing small molecules is 0.5 to 4.0.
[0014] In step S1, when evaporation is performed, the evaporation method is an oil bath, a water bath or a sand bath, and the temperature is 80°C to 130°C.
[0015] In step S1, during calcination, the inert gas atmosphere is nitrogen or argon, the temperature is 500°C to 900°C, the heating rate is 2°C / min to 10°C / min, and the calcination time is 0.5h to 5h.
[0016] In the preparation method of the heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material provided by the present invention, the following characteristics may also be provided: wherein, in step S2, the molar ratio of the cobalt salt to the organic ligand is 0.1 to 10.0.
[0017] In the preparation method of a heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material provided by the present invention, it can also have the following characteristics: wherein, in step S2, when the reaction is carried out, the reaction temperature is 20°C to 70°C, and the reaction time is 1h to 24h.
[0018] In the preparation method of a heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material provided by the present invention, it can also have the following characteristics: wherein, in step S3, the preset gas atmosphere is a nitrogen, argon and H2 / Ar (V%=5:95%) mixed gas atmosphere, and during calcination, the temperature is 500°C~900°C, the heating rate is 2°C / min~15°C / min, and the calcination time is 0.5h~5h.
[0019] In the preparation method of a heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material provided by the present invention, it can also have the following characteristics: wherein the mass ratio of the metal organic framework / heteroatom-doped honeycomb carbon nanocomposite material to tellurium powder is 0.067-15.000.
[0020] In the preparation method of a heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material provided by the present invention, the following characteristics may also be provided: wherein, in step S3, a heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material may be obtained by simultaneously carbonizing and tellurizing a metal organic framework ( / heteroatom-doped honeycomb carbon nanocomposite material and Te powder in one step, or may be obtained by first carbonizing the metal organic framework / heteroatom-doped honeycomb carbon nanocomposite material and then tellurizing it with tellurium powder in two steps.
[0021] The present invention also provides a heteroatom doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material, which is prepared by the preparation method of the heteroatom doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material.
[0022] The present invention also provides an application of the heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material as a positive electrode electrocatalyst for a lithium-sulfur battery.
[0023] The present invention also provides an application method of the above-mentioned heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material as a positive electrode electrocatalyst for a lithium-sulfur battery, which is specifically as follows: a composite material of the heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material and S is used as a cathode, a metal lithium sheet is used as a negative electrode, and the electrolyte is a mixed solution of lithium bis(trifluoromethanesulfonyl)imide and lithium nitrate dissolved in 1,3-dioxolane and ethylene glycol dimethyl ether, and button batteries are assembled in a glove box.
[0024] Functions and Effects of the Invention
[0025] According to the preparation method of the heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material involved in the present invention, the highly exposed oxygen covalently coupled cobalt / cobalt telluride heterostructure is obtained by controllably adjusting the size and distribution of the metal organic framework on the nitrogen-doped honeycomb carbon of oxygen-rich functional groups, and the heterojunction nanocomposite material of the heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride is prepared. The heterojunction nanocomposite material has universality and can also be applied to heterojunction materials constructed by all other metals (Fe, Ni, Zn) and metal compounds (oxides, sulfides, selenides, phosphides and nitrides).
[0026] The heteroatom doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material of the present invention has a simple preparation process, a controllable synthesis method, a high yield, a small material size, abundant active sites, and a high catalytic activity, and is conducive to large-scale commercial production. The prepared heteroatom doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material is applied to the cathode of a lithium-sulfur battery, the sulfur cathode has a high-efficiency catalytic activity, and the lithium-sulfur battery has excellent cycle stability and electrochemical performance.
[0027] The present invention can reduce the size of the catalyst through the confined growth of porous carbon to increase the exposed area and effective utilization rate of the active sites. In addition, considering reducing the resistance between the interfaces of the three-phase heterojunction, the covalent coupling of oxygen is used to achieve rapid charge transfer of the catalyst as a whole. More importantly, the covalent coupling of oxygen atoms can further regulate the electronic configuration of the heterojunction, activate the active atoms at the catalytic sites to the greatest extent, and achieve efficient and controllable catalyst construction. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a scanning electron microscope image of the heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material in Example 1 of the present invention;
[0029] Figure 2 Schematic diagram of the size of the cobalt / cobalt telluride heterostructure nanoparticles in Example 1 of the present invention.
[0030] Figure 3 This is a transmission electron microscope image of the heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material in Example 1 of the present invention;
[0031] Figure 4 is a selected area electron diffraction pattern of the heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material in Example 1 of the present invention;
[0032] Figure 5 is an X-ray diffraction pattern of the heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material in Example 1 of the present invention;
[0033] Figure 6 This is an infrared spectrum of the heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material in Example 1 of the present invention;
[0034] Figure 7 This is an X-ray photoelectron spectrum of the heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material in Example 1 of the present invention;
[0035] Figure 8 The X-ray absorption spectrum (XAFS) of the heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material in Example 1 of the present invention includes the near edge absorption structure (XANES), the extended edge absorption structure (EXAFS) and the wavelet transform analysis results;
[0036] Fig. 9 It is a test data diagram of the electrochemical performance (cyclic voltammetry curve, constant current charge and discharge) of the heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material as a sulfur cathode in a lithium-sulfur button cell in Example 1 of the present invention;
[0037] Fig.10 This is a test data diagram of the electrochemical performance (rate, cycle) of the heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material as a sulfur cathode in a lithium-sulfur battery in Example 1 of the present invention;
[0038] Fig.11 It is a comparison diagram of the first cycle charge and discharge curves obtained at a current density of 0.1C in a lithium-sulfur battery using the heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material as a sulfur cathode in Examples 2-9 of the present invention;
[0039] Fig.12 It is a test data diagram of the electrochemical performance (cyclic voltammetry curve, constant current charge and discharge) of the heteroatomized honeycomb carbon anchored cobalt / cobalt oxide heterostructure nanocomposite material in Comparative Example 1 of the present invention as a sulfur cathode in a lithium-sulfur button cell;
[0040] Fig.13 It is a test data chart of the electrochemical performance (rate, cycle) of the heteroatomized honeycomb carbon anchored cobalt / cobalt oxide heterostructure nanocomposite material in Comparative Example 1 of the present invention as a sulfur cathode in a lithium-sulfur button cell. DETAILED DESCRIPTION
[0041] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the following examples and drawings specifically describe the heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material and its preparation method.
[0042] Example 1
[0043] A method for preparing a heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material of this embodiment comprises the following steps:
[0044] Step S1, dissolving and mixing citrate and nitrogen-containing small molecules, evaporating, carbonizing, and etching to obtain heteroatom-doped honeycomb carbon, the specific process is as follows:
[0045] Dissolve 2.3265g of urea and 20g of sodium citrate in 50mL of water and stir to dissolve. Stir and evaporate at 100°C to obtain a white powder, which is then placed in a tubular furnace and carbonized at 800°C for 2h in a nitrogen atmosphere at a heating rate of 5°C / min. After the tubular furnace is cooled to room temperature, collect the black powder obtained by carbonization, add 4M hydrochloric acid to the black powder obtained above, and continue stirring for 24 hours. Wash with a large amount of deionized water until neutral, and then place in a vacuum oven and dry at 60°C for 12h.
[0046] Step S2, dissolving the heteroatom-doped honeycomb carbon in a mixed solvent and stirring it evenly, then adding an organic ligand to the evenly stirred solution to react, and obtaining a metal organic framework / heteroatom-doped honeycomb carbon nanocomposite material after the reaction, and the specific process is as follows;
[0047] 1.0 mmol of cobalt nitrate hexahydrate and 50 mg of heteroatom-doped honeycomb carbon obtained in step S1 were ultrasonically dissolved in 10 mL of methanol, and then 20 mL of 4 mmol of 2-methylimidazole solution was added. After stirring at room temperature for 8 h, the mixture was washed with methanol three times and dried at 60° C. for 12 h.
[0048] Step S3, placing the metal organic framework / heteroatom doped honeycomb carbon nanocomposite material in a porcelain boat, transferring it to the downstream of the tube furnace, placing tellurium powder upstream of the tube furnace, and calcining it in an inert gas atmosphere to obtain a heteroatom doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material, the specific process is as follows:
[0049] 50 mg of the metal organic framework / heteroatom doped honeycomb carbon nanocomposite material obtained in step S2 was placed in a corundum crucible, transferred to the lower end of a tubular furnace, and 25 mg of tellurium powder was placed on the upper end. In an Ar atmosphere, the heating rate was 2°C / min, and after keeping at 600°C for 3 hours, a heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material was obtained.
[0050] The heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material obtained above is used as a positive electrode electrocatalyst for a lithium-sulfur battery, and the specific application method is as follows:
[0051] A composite material of heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite and S was used as the cathode, a metal lithium sheet was used as the negative electrode, Celgard 2500 was used as the separator, and the electrolyte was a mixed solution of 1.0 M lithium bis(trifluoromethanesulfonyl)imide and 0.15 M lithium nitrate dissolved in 1,3-dioxolane and ethylene glycol dimethyl ether. The cells were assembled into button cells in a glove box.
[0052] The preparation process of the cathode (S / CoTe2 / Co-O-NC) is as follows: the CoTe2 / Co-O-NC heterojunction material and S are heated by a low-temperature melting method at 155°C for 12 hours to obtain a S / CoTe2 / Co-O-NC composite material, and then the S / CoTe2 / Co-O-NC composite material, carbon black (as a conductive agent), and polyvinylidene fluoride (as a binder) are mixed in a mass ratio of 7:2:1, and a dispersant NMP is added. Stir for 12 hours in a sealed and dry environment, and then the stirred slurry is coated on aluminum foil and dried in a vacuum oven at 60 degrees for 12. After drying, it is cut into small discs with a 13mm cutter for standby use.
[0053] Figure 1 These are scanning electron microscope images of the heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material in Example 1 of the present invention, wherein (a) is a scanning electron microscope image at a magnification of 10K, (b) is a scanning electron microscope image at a magnification of 50K, and (c) is a scanning electron microscope image at a magnification of 80K.
[0054] like Figure 1 As shown, the heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material prepared in this example has a typical honeycomb morphology and a highly exposed cobalt / cobalt telluride heterostructure.
[0055] Figure 2 It is a length schematic diagram of the heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material in Example 1 of the present invention.
[0056] like Figure 2 In the heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material prepared in this embodiment, the particles of cobalt / cobalt telluride heterojunction grow tightly on the pore walls of the honeycomb carbon, and the particle size is only 31 nanometers.
[0057] Figure 3 3 is a transmission electron microscope image of the heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material in Example 1 of the present invention, wherein (a) is a low-magnification transmission electron microscope image, and (b) and (c) are high-resolution transmission electron microscope images.
[0058] like Figure 3As shown, the heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite prepared in this embodiment has a distinct cobalt / cobalt telluride heterojunction interface and is evenly distributed on the pore wall of the honeycomb carbon in the form of smaller particles. Figure 3 As shown in (c), the lattice spacings of the (200) and (111) planes of Co and CoTe2 are 0.177 and 0.28 nm, respectively.
[0059] Figure 4 This is a selected area electron diffraction pattern of the heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material in Example 1 of the present invention.
[0060] like Figure 4 As shown in FIG. 1 , the heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite prepared in this embodiment has diffraction crystal forms of two phases, cobalt and cobalt telluride. Figure 3 The analysis results of the high-resolution transmission electron microscopy image in (c) are very consistent. The polycrystalline diffraction rings in the image can be marked as the (111) and (200) crystal planes of Co and the (012), (121) and (111) crystal planes of CoTe2, respectively.
[0061] Figure 5 This is an X-ray diffraction pattern of the heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material in Example 1 of the present invention.
[0062] like Figure 5 As shown, the heteroatom doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material prepared in this embodiment has three physical phase structures of graphite carbon, cobalt and cobalt telluride. The diffraction peaks at 31.9°, 33°, 43.7°, 46.7° and 49.3° in the figure correspond to the (111), (012), (121), (200) and (103) crystal planes of CoTe2 (PDF#74-0245), and the diffraction peaks at 44.2°, 51.5° and 75.8° correspond to the (111), (200) and (220) crystal planes of metallic cobalt (PDF#15-0806), which means the successful formation of CoTe2 / Co junction.
[0063] Figure 6 It is an infrared spectrum of the heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material in Example 1 of the present invention.
[0064] like Figure 6 As shown, the heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material prepared in this embodiment mainly contains C=O, COOH, CC, CN, CO-Co functional groups, which are located at the wavenumbers of 1680, 1652, 1573, 1382 and 1250 cm-1, respectively.
[0065] Figure 7 is an X-ray photoelectron spectrum of the heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material in Example 1 of the present invention, wherein: Figure 7 (a) is the full spectrum of X-ray photoelectron spectrum, (b) is the fine spectrum of C1s of X-ray photoelectron spectrum, (c) is the fine spectrum of N1s of X-ray photoelectron spectrum, (d) is the fine spectrum of O1s of X-ray photoelectron spectrum, (e) is the fine spectrum of Co 2p of X-ray photoelectron spectrum, and (f) is the fine spectrum of Te 3d of X-ray photoelectron spectrum.
[0066] like Figure 7 As shown, the heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material prepared in this embodiment mainly contains five elements: carbon, nitrogen, oxygen, cobalt, and tellurium. Cobalt mainly has 0-valent and 2-valent / 3-valent oxidation states, corresponding to elemental cobalt and cobalt telluride phases, respectively.
[0067] Figure 8 The X-ray absorption spectrum (XAFS) of the heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material in Example 1 of the present invention includes the near edge absorption structure (XANES, Figure a), the extended edge absorption structure (EXAFS, Figures b and c) and the wavelet transform analysis results (Figures d to f);
[0068] like Figure 8 As shown in Figure a, the Co K-edge X-ray absorption near-edge structure (XANES) spectrum edge energy of the heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite (CoTe2 / Co-O-NC) is located between Co foil and CoO, indicating that the average valence state of the Co element is between 0 and +2. From the Fourier transform (FT) k 3 The weighted Co k-edge extended X-ray absorption fine structure (EXAFS) spectrum (Fig. b) shows that the peaks and scattering paths of CoTe2 / Co-O-NC are different from those of CoO and Co2O3, further indicating that no metallic Co-O bonds are formed in CoTe2 / Co-O-NC. The peaks at 10 and 11 belong to Co-O, Co-Co and Co-Te bond coordination, respectively. The bond length of Co-O in CoTe2 / Co-O-NC is shorter than that in CoO, indicating that Co and O are only covalently connected. Quantitatively considering these three backscattering paths, the least squares EXAFS curve fitting analysis was performed (Figure c), and the bond distances of Co-O, Co-Te and Co-Co were determined to be 1.99, 2.52 and 1.67 mm, respectively. In addition, we also explored the wavelet transform (WT) EXAFS contour map of CoTe2 / Co-O-NC, proving that there is no CoO species in CoTe2 / Co-O-NC, as shown in Figure df, which is different from the Co-Co coordination characteristics.
[0069] Compared with the WT contour map of CoO, the band corresponding to Co-Te / Co-Co appears in the WT contour map of CoTe2 / Co-O-NC, but it does not have the coordination characteristics of Co-Co in Co foil and CoO, indicating that there is no CoO species in CoTe2 / Co-O-NC, which fully proves the covalent coupling between Co-O. Compared with the WT contour map of CoO, the band corresponding to Co-Te / Co-Co appears in the WT contour map of CoTe2 / Co-O-NC, but it does not have the coordination characteristics of Co-Co in Co foil and CoO, indicating that there is no CoO species in CoTe2 / Co-O-NC, which fully proves the covalent coupling between Co-O.
[0070] Fig. 9 This is a graph showing the electrochemical performance test data of the heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material in Example 1 of the present invention as a sulfur host in a lithium-sulfur battery. Fig. 9 (a) is the cyclic voltammetry curve test data, and (b) is the constant current charge and discharge test data.
[0071] like Fig. 9 As shown in Figure 2, the heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite as a catalytic host for sulfur has a strong redox peak current (CV results show two reduction peaks (Ⅰ and Ⅱ) and one oxidation peak (Ⅲ), corresponding to S8 2- →S4 2- , S4 2- →Li2S2 / Li2S and Li2S2 / Li2S→S8) and the typical charge-discharge platform, demonstrating the efficient catalytic conversion performance of heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposites for lithium polysulfide.
[0072] Fig.10 This is a graph showing the electrochemical performance test data of the heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material in Example 1 of the present invention as a sulfur host in a lithium-sulfur battery. Fig.10 (a) is the rate data of lithium-sulfur batteries tested at different current densities, and (b) is the cycle stability diagram tested at a current density of 2C.
[0073] like Fig.10As shown, the heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material, as a catalytic host for sulfur, exhibits very excellent rate performance and cycle stability. As can be seen from Figure a, the battery has good cycle stability at different current densities. When the high current of 3C drops sharply to the low current of 0.1C, the battery can still operate smoothly, and the capacity loss is also small, which reflects the excellent electrode structure stability and electrochemical cycle reversibility. Figure b shows the cycle stability of the lithium-sulfur battery tested at a high current density of 2C for 300 cycles. The results show a cycle attenuation rate of 0.023% per cycle and a coulombic efficiency of nearly 100%. This also shows that the heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material as a catalytic host for sulfur has excellent catalytic sulfur conversion activity, which can significantly improve the electrochemical performance of lithium-sulfur batteries.
[0074] In summary, the method of the heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material of the present invention can successfully prepare a covalently coupled cobalt / cobalt telluride heterostructure nanocomposite material having a typical honeycomb morphology and high exposed oxygen, and the composite material has excellent catalytic activity and stability, can be used as an electrocatalyst for the sulfur positive electrode of an efficient lithium-sulfur battery, achieves an ultra-high energy density of the lithium-sulfur battery, and has very considerable commercial application potential.
[0075] Example 2
[0076] In this embodiment, based on the preparation conditions of Example 1, the sodium citrate in step S1 is replaced by ammonium citrate to prepare a heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material.
[0077] Example 3
[0078] In this embodiment, based on the preparation conditions of Example 1, the urea in step S1 is replaced with melamine to prepare a heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material.
[0079] Example 4
[0080] In this embodiment, based on the preparation conditions of Example 1, the carbonization at 800° C. for 2 h in a nitrogen atmosphere in step S1 was replaced by calcination at 500° C. for 5 h to prepare a heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material.
[0081] Example 5
[0082] In this embodiment, based on the preparation conditions of Example 1, the heating rate of 5°C / min in step S1 was replaced by a heating rate of 2°C / min to prepare a heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material.
[0083] Example 6
[0084] In this example, based on the preparation conditions of Example 1, 1.0 mmol of cobalt nitrate hexahydrate in step S2 was replaced with 2.0 mmol to prepare a heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material.
[0085] Example 7
[0086] In this embodiment, based on the preparation conditions of Example 1, the 25 mg of tellurium powder in step S3 was changed to 5 mg to prepare a heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material.
[0087] Example 8
[0088] In this embodiment, based on the preparation conditions of Example 1, the heating rate in step S3 is 2°C / min, and the temperature is kept at 600°C for 3 hours, and the heating rate is 10°C / min, and the temperature is kept at 600°C for 5 hours to prepare a heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material.
[0089] Example 9
[0090] In this embodiment, based on the preparation conditions of Example 1, the heating rate in step S3 is 2°C / min, and the temperature is kept at 600°C for 3 hours, and the heating rate is 5°C / min, and the temperature is kept at 700°C for 1 hour to prepare a heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material.
[0091] Fig.11 Under the preparation conditions of Example 2-9, a heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material was prepared as the cathode of a lithium-sulfur battery. A comparison chart of the first cycle charge and discharge curves obtained at a current density of 0.1C is shown. It can be seen from the figure that the specific capacities measured in Examples 2-9 are all lower than the specific capacity measured in Example 1.
[0092] Comparative Example 1
[0093] In this comparative example, a heteroatomized honeycomb carbon anchored high exposed cobalt / cobalt oxide heterostructure nanocomposite material is disclosed, and the preparation method is as follows:
[0094] Step S1, dissolving 30 mmol sodium citrate and 15 mmol urea in 30 mL water, evaporating the solvent at 110° C. in an oil bath, grinding to obtain a white powder, calcining the obtained white powder at 800° C. in a nitrogen atmosphere in a tubular furnace for 1 h, then etching with dilute hydrochloric acid to remove excess products, filtering, washing with water, and drying to obtain heteroatomized honeycomb carbon.
[0095] Step S2, ultrasonically treating 1.0 mmol of cobalt nitrate hexahydrate and 50 mg of heteroatomized honeycomb carbon obtained in step S1 in 20 mL of methanol, stirring and dispersing them uniformly, and then adding 20 mL of a methanol solution containing 4.0 mmol of 2-methylimidazole. After reacting at room temperature for 6 hours, centrifugation and methanol washing are performed to obtain a metal organic framework / heteroatomized honeycomb carbon nanocomposite material.
[0096] Step S3, placing the metal organic framework / heteroatomized honeycomb carbon nanocomposite material obtained in step S2 in a porcelain boat and transferring it to a tubular furnace, heating it at a rate of 2°C / min, and calcining it at 700°C in a nitrogen atmosphere for 2h to obtain a heteroatomized honeycomb carbon anchored high exposed cobalt / cobalt oxide heterostructure nanocomposite material.
[0097] Fig.12 This is a graph showing the electrochemical performance test data of the heteroatomized honeycomb carbon anchored cobalt / cobalt oxide heterostructure composite material in Comparative Example 1 of the present invention as a sulfur host in a lithium-sulfur battery. Fig.12 (a) is the rate data of lithium-sulfur batteries tested at different current densities, and (b) is the cycle stability diagram tested at a current density of 2C.
[0098] Compared with the preparation method of a heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material and its application specification, Figure 8 , (a) is the cyclic voltammetry test data, (b) is the constant current charge and discharge test data. Figure 8 As shown in a, the three peaks Ⅰ, Ⅱ and Ⅲ correspond to S8 2- →S4 2- , S4 2- →Li2S2 / Li2S and Li2S2 / Li2S→S8. Compared with the CV test of S / CoTe2 / Co-O-NC electrode, the peak current of S / Co-CoO / HLNPC is significantly reduced, and the voltage difference between peak II and peak III is also significantly increased, indicating that the catalytic conversion performance of S / Co-CoO / HLNPC for lithium polysulfide is significantly weakened, which is obviously inferior to S / CoTe2 / Co-O-NC electrode. Figure 8 b is the constant current charge and discharge curve of S / Co-CoO / HLNPC cathode at a current density of 0.1C. It can be seen from the figure that the charge and discharge specific capacity of the battery is reduced by 536mAh g-1 compared with the S / CoTe2 / Co-O-NC cathode, the polarization of the battery increases, and the electrochemical performance is significantly reduced.
[0099] Fig.13 This is a graph showing the electrochemical performance test data of the heteroatomized honeycomb carbon anchored cobalt / cobalt oxide heterostructure composite material in Comparative Example 1 of the present invention as a sulfur host in a lithium-sulfur battery. Fig.13(a) is the rate data of lithium-sulfur batteries tested at different current densities, and (b) is the cycle stability diagram tested at a current density of 2C.
[0100] In Figure a, when S / CoTe2 / Co-O-NC is used as the sulfur cathode of the lithium-sulfur battery, the specific capacities at current densities of 0.1C, 0.2C, 0.3C, 0.5C, 1C, 2C, and 3C are 1468, 1156, 1053, 948, 790, 695, and 597 mAh g, respectively. -1 However, when S / Co-CoO / HLNPC was used as the sulfur cathode of lithium-sulfur battery, the specific capacities at current densities of 0.1C, 0.2C, 0.3C, 0.5C, 1C, 2C and 3C were 991, 680, 590, 480, 454, 385 and 111 mAh g -1 , which is significantly worse than the former. In Figure b, at a current density of 2C, the S / CoTe2 / Co-O-NC cathode cycles 300 times, with a capacity decay rate of 0.023% per cycle, while the S / Co-CoO / HLNPC cathode cycles 300 times, with a capacity decay rate of 1.38% per cycle, indicating that the S / Co-CoO / HLNPC cannot effectively inhibit the shuttle of lithium polysulfide and catalyze the conversion of lithium polysulfide, and the cycle stability of the battery is also significantly worse than the former, indicating that the electrochemical performance of the S / Co-CoO / HLNPC is significantly worse than that of the S / CoTe2 / Co-O-NC cathode.
[0101] Functions and Effects of the Embodiments
[0102] According to Examples 1-9 and Comparative Example 1, it can be seen that through the preparation method of a heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material of the present invention, it is possible to simply and efficiently prepare an oxygen covalently coupled high-exposed cobalt / cobalt telluride heterostructure nanocomposite material. The composite material has a typical honeycomb morphology and highly exposed cobalt / cobalt telluride heterojunction catalytic active sites, and can be used as a high-performance sulfur positive electrode catalytic material for lithium-sulfur batteries. It has excellent performance and good stability, and has great application advantages in the commercial development of lithium-sulfur batteries. In addition, the material of the present invention has the advantages of porous structure and high efficiency of active sites, and also has broad development prospects and application space in other types of energy catalysis and environmental improvement fields such as water pollution control.
[0103] Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing a heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material, characterized in that: The steps include: Step S1, dissolving and mixing citrate and nitrogen-containing small molecules, and subjecting them to evaporation, carbonization, and etching to obtain heteroatom-doped honeycomb carbon; Step S2, dissolving the heteroatom-doped honeycomb carbon in a mixed solvent and stirring evenly, then adding an organic ligand to the evenly stirred solution to react, and obtaining a metal organic framework / heteroatom-doped honeycomb carbon nanocomposite material after the reaction; Step S3, placing the metal organic framework / heteroatom doped honeycomb carbon nanocomposite material in a porcelain boat, transferring it to the downstream of a tube furnace, placing tellurium powder upstream of the tube furnace, and calcining it in an inert gas atmosphere to obtain a heteroatom doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material, Wherein, in step S3, the mass ratio of the metal organic framework / heteroatom doped honeycomb carbon nanocomposite material to the tellurium powder is 1.5-2.
5.
2. The method for preparing a heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material according to claim 1, characterized in that: in, In step S1, the molar ratio of the citrate to the nitrogen-containing small molecule is 0.5 to 4.
0. In step S1, when evaporation is performed, the evaporation method is an oil bath, a water bath or a sand bath, and the temperature is 80°C to 130°C. In step S1, during calcination, the inert gas atmosphere is nitrogen or argon, the temperature is 500°C to 900°C, the heating rate is 2°C / min to 10°C / min, and the calcination time is 0.5h to 5h.
3. The method for preparing a heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material according to claim 1, characterized in that: in, In step S2, the molar ratio of the cobalt salt to the organic ligand is 0.1 to 10.
0.
4. The method for preparing a heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material according to claim 1, characterized in that: in, In step S2, when the reaction is carried out, the reaction temperature is 20°C to 70°C, and the reaction time is 1h to 24h.
5. The method for preparing a heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material according to claim 1, characterized in that: in, In step S3, the preset gas atmosphere is a mixed gas atmosphere of nitrogen, argon and H2 / Ar (V%=5:95%). During calcination, the temperature is 500°C to 900°C, the heating rate is 2°C / min to 15°C / min, and the calcination time is 0.5h to 5h.
6. The method for preparing a heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material according to claim 1, characterized in that: in, The mass ratio of the metal organic framework / heteroatom doped honeycomb carbon nanocomposite material to tellurium powder is 0.067-15.
000.
7. The method for preparing a heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material according to claim 1, characterized in that: in, In step S3, a heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material can be obtained by simultaneously carbonizing and tellurizing a metal organic framework ( / heteroatom-doped honeycomb carbon nanocomposite material and Te powder in one step, or by first carbonizing the metal organic framework / heteroatom-doped honeycomb carbon nanocomposite material and then tellurizing it with tellurium powder in two steps.
8. The heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material according to claim 1, characterized in that: The nanocomposite material is prepared by the method for preparing a heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material as described in any one of claims 1 to 7.
9. Use of the heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material as claimed in claim 8 as a positive electrode electrocatalyst for lithium-sulfur batteries.
10. The use of a heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite material as a positive electrode electrocatalyst for lithium-sulfur batteries according to claim 9, characterized in that: The application method is as follows: The composite material of the heteroatom-doped honeycomb carbon covalently coupled cobalt / cobalt telluride heterojunction nanocomposite and S is used as the cathode, the metal lithium sheet is used as the negative electrode, and the electrolyte is a mixed solution of lithium bis(trifluoromethanesulfonyl)imide and lithium nitrate dissolved in 1,3-dioxolane and ethylene glycol dimethyl ether, and a button battery is assembled in a glove box.
Citation Information
Patent Citations
Nitrogen and sulfur co-doped carbon nano-tube composite material as well as preparation method and application thereof
CN114400340A
CoTe2 / CoP-Ti composite material and preparation method thereof
CN115094455A
Preparation method and application of cobalt-based nanocluster inlaid honeycomb carbon composite material
CN116102075A
Metal organic framework derived cobalt ditelluride-reduced graphene oxide composite material as well as preparation method and application thereof
CN116314710A
Heteroatomized honeycomb carbon anchored cobalt / cobalt oxide heterostructure nano composite material and preparation method thereof
CN116364950A